The emergence of gender differences in consumer socialization among college students - Falahati, Leila; Paim, Laily (Marsland Press, 2011)
This study examines the gender differences in consumer socialization among college students. The sample comprised 2,430 students in six public and five private universities across Malaysia, which were randomly selected for the study. A self-administered questionnaire was used as the data collection method. The results revealed gender differences in consumer socialization, in which male students’ perceived earlier socialization regarding financial matters. In addition, the results indicated that females are socialized earlier in receiving allowances and owning bank accounts while males are socialized earlier in financial activity and financial assets.